A phenomenographic study of students’ conceptions of formal research procedures - Yeo, Jesvin Puay-Hwa (2016)
The purpose of this paper is to explore the potential use of formal research procedures in design research. Formal research procedures refer to the conventional approaches currently undertaken when conducting research in academic disciplines such as science and the humanities. This paper uses the phenomenography method by Hasselgren and Beach as the basis of its research design. This paper employed eight-step analysis process adopted from Creswell (2013) to analyze the interview transcripts of the participants. Focusing on visual communication studies at undergraduate level, this paper is a documentation of development and implementation of the formal research procedures on eighteen design research proposals. It shares the insight on how students experience, interpret, perceive or conceptualize various aspects of design research to capture the different ways in which design research is conceived by them. The study resulted in the identification of three conceptions defining the variation in the ways in which formal research procedures is understood: process conception, meaning conception and journey conception. The findings have affirmed aspects of formal research procedures and represent a first step in explaining the different ways in which visual communication students conceive design research.